ANALISIS DAMPAK COVID-19 TERHADAP KUANTITAS NASABAH PRODUK PENDANAAN (Studi pada Bank Muamalat Indonesia Kantor Cabang Pembantu Lhokseumawe) - Juliana Putri; Fitria Andriani; Erawati Erawati (Al-Ahkam: Jurnal Syariah dan Peradilan Islam, 2022)
Covid-19 at Bank Muamalat has also made customers from funding products experience a decrease in customer quantity. The spread of the corona virus and implementing social restrictions have weakened the performance and capacity of banks, especially funding, because one of the marketing strategies of Bank Muamalat Lhokseumawe Sub-Branch Office is the door to door method. Where this method is Bank Muamalat's way to attract customers. The purpose of this study was to determine the impact of Covid-19 on the quantity of funding product customers at Bank Muamalat Indonesia Lhokseumawe Sub-Branch Office by comparing before and during Covid-19. In this study, researchers want to see the quantity of customers in funding products which include savings products, current accounts, and deposits before and during Covid-19. The test uses a different test, namely the paired sample t-test and the sign-wixolcon test. The results obtained that there are significant differences in the number of customers in savings products, current accounts and time deposits. From the results, it can be concluded that there is an impact of Covid-19 on the quantity of funding product customers at Bank Muamalat Indonesia Lhokseumawe Sub-Branch Office